Square Root Functional Equation on Positive Cones (Analysis in Theory and Applications, 2013)
A square root functional equation on positive cones of $C^{*}$-algebras is introduced and its solution and Hyers-Ulam-Rassias stability are investigated.
Keywords: Hyers-Ulam stability; fixed point; additive functional equation.